2012
DOI: 10.1111/j.1365-294x.2012.05545.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA from soil mirrors plant taxonomic and growth form diversity

Abstract: Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next-generation DNA sequencing, we tested an approach we call metabarcoding: high-throughput and simultaneous taxa identification based on a very short (usually <100 base pairs) but informative DNA fragment. Short DNA fragments allow the use of degraded DNA from environmental samples. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
302
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(314 citation statements)
references
References 43 publications
10
302
0
2
Order By: Relevance
“…This result highlights the need of a relatively high amount of mammalian DNA that was transferred to the lake to be detected in the sediments (see Supplementary Discussion about mammalian DNA detection) and shows that the absence of DNA in lake sediments should be treated with caution, as this does not necessarily highlight the absence of the targeted species. In contrast, no cattle herd is currently in the catchment, but we record the presence of cow DNA in one of eight PCRs of the recent lake sediments, which may be explained by sporadic contamination or stocking of older cow DNA in soils because it is known that DNA can persist in alpine soils for at least 50 years 34 . Thus, these results, which are contradictory to expectations, reveal that lake sedDNA allows the reconstruction of past livestock history with a high level of confidence when the stocking rate (in animal unit per day ha À 1 ) is relatively high and/or the practice induces important transfer of domestic mammal DNA (mainly from faeces, skin flakes and chitinous material 35 ) to the lake.…”
Section: Discussionmentioning
confidence: 94%
“…This result highlights the need of a relatively high amount of mammalian DNA that was transferred to the lake to be detected in the sediments (see Supplementary Discussion about mammalian DNA detection) and shows that the absence of DNA in lake sediments should be treated with caution, as this does not necessarily highlight the absence of the targeted species. In contrast, no cattle herd is currently in the catchment, but we record the presence of cow DNA in one of eight PCRs of the recent lake sediments, which may be explained by sporadic contamination or stocking of older cow DNA in soils because it is known that DNA can persist in alpine soils for at least 50 years 34 . Thus, these results, which are contradictory to expectations, reveal that lake sedDNA allows the reconstruction of past livestock history with a high level of confidence when the stocking rate (in animal unit per day ha À 1 ) is relatively high and/or the practice induces important transfer of domestic mammal DNA (mainly from faeces, skin flakes and chitinous material 35 ) to the lake.…”
Section: Discussionmentioning
confidence: 94%
“…For example, eDNA collected in terrestrial soil samples have been used to assess earthworm diversity which can relate to healthy ecosystem function (Bienert et al 2012). Yoccoz et al 2012 suggested that soil eDNA could also enable unprecedented rapid assessment of local plant communities and community-level responses to climate change. In terms of detection capabilities, the success of eDNA monitoring in aquatic environments has compared well with more traditional kick net sampling of benthic macroinvertebrates in Switzerland streams (Mächler et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With developments in high-throughput sequencing technologies and bioinformatics pipelines, it is now possible to sequence a single genetic locus en masse from the environment and delimit species in large scale environmental (eDNA) metabarcoding surveys (2,3). Such eDNA surveys have been used to describe the diversity of microorganisms (4), macrofauna (5), fungi (6), and plants (7) in previously understudied habitats, such as the soil biota (8), sediments (9), and water (5,10). Faced with these technological advances, it is now more important than ever to evaluate the reliability of the genetic loci used for DNA taxonomy, and to assess the congruence of their results with morphological taxonomy.…”
mentioning
confidence: 99%